Mixing in microchannels based on hydrodynamic focusing and time-interleaved segmentation : modelling and experiment - Nguyen, Nam-Trung (2014)
This paper theoretically and experimentally investigates a micromixer based on combined hydrodynamic focusing and time-interleaved segmentation. Both hydrodynamic focusing and time-interleaved segmentation are used in the present study to reduce mixing path, to shorten mixing time, and to enhance mixing quality. While hydrodynamic focusing reduces the transversal mixing path, time-interleaved sequential segmentation shortens the axial mixing path. With the same viscosity in the different streams, the focused width can be adjusted by the flow rate ratio. The axial mixing path or the segment length can be controlled by the switching frequency and the mean velocity of the flow. Mixing ratio can be controlled by both flow rate ratio and pulse width modulation of the switching signal. This paper first presents a time-dependent two-dimensional analytical model for the mixing concept. The model considers an arbitrary mixing ratio between solute and solvent as well as the axial Taylor–Aris dispersion. A micromixer was designed and fabricated based on lamination of four polymer layers. The layers were machined using a CO2 laser. Time-interleaved segmentation was realized by two piezoelectric valves. The sheath streams for hydrodynamic focusing are introduced through the other two inlets. A special measurement set-up was designed with synchronization of the mixer's switching signal and the camera's trigger signal. The set-up allows a relatively slow and low-resolution CCD camera to freeze and to capture a large transient concentration field. The concentration profile along the mixing channel agrees qualitatively well with the analytical model. The analytical model and the device promise to be suitable tools for studying Taylor–Aris dispersion near the entrance of a flat microchannel.